Analysis of Learning Difficulties in Biology Material Through The Implementation of Merdeka Curriculum in First Grade (X Class) Senior High School Students of SMA Negeri 2 Percut Sei Tuan - Nurul Jannah Siregar; Rohani Rohani (Universitas Labuhanbatu, 2024)
The Ministry of Education, Culture, Research and Technology (Kemendikburistek) issued a policy in the development of the Independent Curriculum which is given to educational units as an additional option in order to restore learning during 2022-2024 and improve the quality of education.Based on observations and interviews conducted at SMA Negeri 2 Percut Sei Tuan, North Sumatra.The implementation of the independent curriculum has not been carried out thoroughly, because there are still several factors or obstacles to student difficulties in the learning process. The method used in this research is a qualitative method with descriptive research.This research was conducted at SMA Negeri 2 Percut Sei Tuan.The population in this study were the biology teachers and all students of First grade an each class totaling 36 students. Based on research conducted by researchers at SMA Negeri 2 Percut Sei Tuan, several student difficulties in learning biology through the implementation of the independent curriculum were found, namely internal factors and external factors